Unconventional green - Zaghini, Andrea (Journal of Corporate Finance, 2024)
We analyse the effects of the Pandemic Emergency Purchase Programme (PEPP) launched by the ECB after the burst of the Covid-19 pandemic. The effects of the programme were different from the previous asset purchases. The PEPP significantly reduced the yield on bonds that at the same time were eligible to the programme and showed a green label. Via a triple difference estimator, we show that this effect is additional to the outperformance of greens vs non-green bonds that also occurred in the set of non-eligible bonds. All in all, the estimated impact stands at 51 basis points, a value that is significant also from an economic point of view: around 20 per cent of the cost of issuing a bond. From a climate change perspective, this evidence suggests that asset purchase programmes are an effective way of supporting firms financing climate-friendly investments on the bond market. In addition, we find that the issuers that benefitted most from the PEPP improved their ESG performance to a larger extent than other issuers.